2007
DOI: 10.3354/dao01808
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent expression of immune-relevant genes in rainbow trout following Yersinia ruckeri vaccination

Abstract: The gene expression of immune-relevant genes in rainbow trout Oncorhynchus mykiss following vaccination with a bacterin of Yersinia ruckeri, a bacterial pathogen causing enteric red mouth disease (ERM), was investigated at 5, 15, and 25°C. Rainbow trout were immunized by i.p. injection of a water-based Y. ruckeri (serotype O1) bacterin, and gene expression profiles were compared to control groups injected with phosphate buffered saline (PBS). Blood and tissue samples (spleen and head kidney) were taken for sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
55
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 42 publications
6
55
0
2
Order By: Relevance
“…Our comparative approach using two ERM vaccines with different efficacies and a nonimmunized infected control group allowed us to correlate protection to cellular and humoral events in the hosts. Although it would be expected that adaptive elements should play a prominent role in protection, we observed that factors often related to the innate immune response (SAA, complement factors, lysozyme, and macrophage activity) (6,(33)(34)(35) were found in vaccinated fish at higher levels than were seen in nonimmunized fish. This indicated that innate effector molecules are also of importance for pathogen elimination even in vaccinates in the early phase of infection.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our comparative approach using two ERM vaccines with different efficacies and a nonimmunized infected control group allowed us to correlate protection to cellular and humoral events in the hosts. Although it would be expected that adaptive elements should play a prominent role in protection, we observed that factors often related to the innate immune response (SAA, complement factors, lysozyme, and macrophage activity) (6,(33)(34)(35) were found in vaccinated fish at higher levels than were seen in nonimmunized fish. This indicated that innate effector molecules are also of importance for pathogen elimination even in vaccinates in the early phase of infection.…”
Section: Discussionmentioning
confidence: 62%
“…Measurements of (4,33,34). Our comparative approach using two ERM vaccines with different efficacies and a nonimmunized infected control group allowed us to correlate protection to cellular and humoral events in the hosts.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature influences biological processes, mainly for fish immune responses (Padron et al, 2000;Raida, & Buchmann, 2007). In this study, we analyzed the effect of temperature changes on the expression of antiviral genes against IPNV.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, immune-related functions such as endocytosis (Padron, Bizeau, & Hazel, 2000), immune gene transcription (Raida, & Buchmann, 2007), immunoglobulins concentration (Suzuki, Otaka, Sato, Hou, & Aida, 1997;Nikoskelainen, Bylund, & Lilius, 2004), and C-reactive protein (Kodama et al, 2004) have been reported to be dependent on the ambient temperature.…”
mentioning
confidence: 99%
“…Strains lacking this gene have decreased virulence and confer a high level of protection in rainbow trout fry when they are used for vaccination (4). Other putative virulence factors of F. psychrophilum include a lipopolysaccharide with an unusual O-antigen structure (16, 33), glycocalyx (29), and the tlpB (thiol oxidoreductase-like protein gene) locus, which is involved in gliding motility, growth on iron-depleted media, and extracellular proteolytic activity (3).Decreasing the water temperature below the optimum for a particular species of fish usually reduces or delays the immune response (11,40). In rainbow trout, the immunologically nonpermissive temperature is approximately 4°C (10), while the physiologically optimum temperature is 15°C (40).…”
mentioning
confidence: 99%